Type IV pili of Acidithiobacillus ferrooxidans can transfer electrons from extracellular electron donors. (26th February 2013) - Li, Yongquan; Li, Hongyu
<x xml:space="preserve">Abstract</x> Studies on Acidithiobacillus ferrooxidans accepting electrons from Fe(II) have previously focused on cytochrome c. However, we have discovered that, besides cytochrome c, type IV pili (Tfp) can transfer electrons. Here, we report conduction by Tfp of A. ferrooxidans analyzed with a conducting‐probe atomic force microscope (AFM). The results indicate that the Tfp of A. ferrooxidans are highly conductive. The genome sequence of A. ferrooxidans ATCC 23270 contains two genes, pilV and pilW, which code for pilin domain proteins with the conserved amino acids characteristic of Tfp. Multiple alignment analysis of the PilV and PilW (pilin) proteins indicated that pilV is the adhesin gene while pilW codes for the major protein element of Tfp. The likely function of Tfp is to complete the circuit between the cell surface and Fe(II) oxides. These results indicate that Tfp of A. ferrooxidans might serve as biological nanowires transferring electrons from the surface of Fe(II) oxides to the cell surface.